Subjective Well Being and the Impact of Climate Change - Carola Grün; Nicole Grunewald (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
We analyze the relationship between subjective well-being as a non-income welfare measure and climate variables such as temperature, precipitation rates or cloud covered days. Therewith, we estimate the effects from events related to climate change on subjective well-being and point out possible welfare losses and gains due to climate change. Even though that there is a growing number of research done on well-being in terms of income measures and climate change, there is only little research done on the effect of climate change and non-income measures such as subjective well-being. Further those studies lack some comparison. Except Rehdanz and Maddison (2005) all studies turn to national analyses when analyzing the influence of climate on subjective well-being. So far there are very few studies on middle- and none on low-income countries done, but at the same time extreme weather events may especially affect people in poorer countries. Therefore, we test this relationship for low and middle-income countries in Latin America and put the results in comparison to earlier studies. We apply survey data from the World Value Survey and Latinobarometro which cover the years 1985- 2008. In a panel study we estimate subjective well-being in Latin America and control for gender, age, marital status and income. Further we introduce climate variables such as the deviation from the mean temperature and precipitation rates as to analyze how the rising variance in climate affects subjective well being.
Keywords: I30; Q54; 330; Subjective Well Being; Climate Change